Engine test bench feasibility for the study and research of real driving cycles: Pollutant emissions uncertainty characterization. (July 2022) - Luján, José Manuel; Bermudez, Vicente; Pla, Benjamín; Redondo, Fernando
The future of Internal Combustion Engines in the automotive sector seems uncertain, to some extent due to the recent changes in type approval regulations. Current regulations have considerably reduced the engine pollutant emissions limits, as well as introduced more demanding testing conditions. The introduction of real driving cycles presented a challenging issue for car manufacturers when homologating their vehicles, since the traditional and undemanding NEDC (New European Driving Cycle) certification cycle has been replaced by sever cycles as WLTC (World Light Duty Test Cycle) and RDE (Real Driving Emissions). This document presents a methodology for implementing a RDE cycle in an engine test bench. Even knowing that the essence of RDE regulation is to assess actual driving conditions, reproducing RDE cycles in a test bench is of great interest, since the controlled and reproducible conditions that can be achieved in a laboratory lead to valuable information to understand engine behavior in real driving conditions, and therefore contribute to engine development. This document applies the most recent European Community regulation and sets the essential steps to carry out a RDE cycle in an engine test bench. Once the WLTC and RDE cycles were implemented, this study analyses the uncertainty and repeatability of the values obtained in successive repetitions of the test, carried out under the same conditions. Uncertainty values are obtained on the most representative parameters of engine operation, as well as pollutant emissions. One of the most relevant contributions of this study is to obtain the uncertainties of type approval pollutant emissions. As an example, the uncertainty obtained by applying the methodology described in this article on nitrogen oxide emissions (NOx), considered one of the most relevant pollutant emissions of diesel engines, has been extremely reduced, obtaining values of 3.13% and 3.9%, respectively for the RDE and WLTC cycles.